1996
DOI: 10.1056/nejm199603213341201
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer and Other Second Neoplasms after Childhood Hodgkin's Disease

Abstract: The risk of solid tumors, especially breast cancer, is high among women who were treated with radiation for childhood Hodgkin's disease. Systematic screening for breast cancer could be important in the health care of such women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
459
5
15

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 842 publications
(497 citation statements)
references
References 41 publications
18
459
5
15
Order By: Relevance
“…19 Follow up of 1380 children with HD aimed at determining the risk of occurrence of secondary neoplasms has shown that irradiation in childhood is associated with the highest risk for development of radiation-induced breast cancer. 8 Similar findings have been reported by Clemons et al, 20 establishing that the highest risk of developing breast cancer is by irradiation between puberty and the age of 30.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…19 Follow up of 1380 children with HD aimed at determining the risk of occurrence of secondary neoplasms has shown that irradiation in childhood is associated with the highest risk for development of radiation-induced breast cancer. 8 Similar findings have been reported by Clemons et al, 20 establishing that the highest risk of developing breast cancer is by irradiation between puberty and the age of 30.…”
Section: Discussionsupporting
confidence: 79%
“…Breast cancer was the most common solid tumor (standardized incidence ratio 75.3; 95 percent confidence interval, 44.9-118.4), with an estimated actuarial incidence in women that approached 35 percent (95 percent confidence interval, 17.4-52.6 percent) by 40 years of age. 8 To solve this problem, scientific research in recent years has focused on the following areas:…”
Section: Background and Aimmentioning
confidence: 99%
“…40 However, in other reports, the median time of survival for secondary NHL was only 2.5 months. 41 Despite the large sample size and long follow-up of the SEER-9 registry cohort, our study has several limitations that should be considered while interpreting results. As the registry has no information on biologic features of primary malignancies, diagnosis of secondary hematological malignancies may be overestimated.…”
Section: Discussionmentioning
confidence: 94%
“…Two patients devel- It has been well documented that radiation therapy can induce secondary malignancies at the site of exposure. 2,42,43 In our analysis, Patients 1 and 6 received radiotherapy for local control of the primary OS in addition to systemic chemotherapy, before the development of SMN (fibrosarcoma and maxillary astrocytoma, respectively) that arose in the radiation field. Patient 13 received external beam radiation (3500 cGy) at age 1 year for his retinoblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…A significant amount of information regarding second malignancies following treatment of Hodgkin disease, [1][2][3] retinoblastoma, 4 -6 and acute lymphoblastic leukemia (ALL) 7 is available because a good cure rate has been achieved for many years, resulting in many long-term survivors.…”
mentioning
confidence: 99%